2018
DOI: 10.1177/1049732318808245
|View full text |Cite
|
Sign up to set email alerts
|

Autism Disparities: A Systematic Review and Meta-Ethnography of Qualitative Research

Abstract: Racial, ethnic, and socioeconomic disparities associated with autism spectrum disorder (ASD) are evident across many service domains including access to early assessment, diagnosis, and therapeutic interventions. To better understand the complex social and structural factors contributing to these disparities, this article offers a systematic review of peer-reviewed qualitative research conducted from 2010 to 2016 in the United States that investigates autism disparities experienced by marginalized communities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 57 publications
2
54
1
Order By: Relevance
“…Some researchers have begun to develop culturally relevant ASD interventions to meet the needs of diverse communities in the US, including Black and Latinx children with ASD, as racial and ethnic disparities persist even after controlling for socioeconomic differences (29,31,79). The majority of US studies have investigated service disparities between Black, Latinx, and White children and their families, although emerging research has identified barriers for Asian immigrant communities as well (80,81). Globally, researchers have culturally adapted EBPs, for example using a task-shifting approach in South Asia, and a combined parent-teacher training model for refugee families in Turkey (27,82).…”
Section: Using An Implementation Science Framework To Support Communimentioning
confidence: 99%
“…Some researchers have begun to develop culturally relevant ASD interventions to meet the needs of diverse communities in the US, including Black and Latinx children with ASD, as racial and ethnic disparities persist even after controlling for socioeconomic differences (29,31,79). The majority of US studies have investigated service disparities between Black, Latinx, and White children and their families, although emerging research has identified barriers for Asian immigrant communities as well (80,81). Globally, researchers have culturally adapted EBPs, for example using a task-shifting approach in South Asia, and a combined parent-teacher training model for refugee families in Turkey (27,82).…”
Section: Using An Implementation Science Framework To Support Communimentioning
confidence: 99%
“…However, ASD research has disproportionately low representation from populations outside of the United States and Europe (7). Even in countries such as the United States, where the majority of ASD research has been conducted, there is limited representation from minority groups, multilingual families, and participants with lower socioeconomic status (8).…”
mentioning
confidence: 99%
“…Females with ASD–3 have been suspected as having different clinical phenotypes and psychosocial factors from males with the same diagnosis (Lai et al, 2015) and arguably are exposed to different sociocultural environments and expectations in most cultures (Lips, 2017). Gender, ethnic/cultural, and socioeconomic differences are, therefore, likely to be worthwhile factors for investigation, specifically in terms of how these differences may moderate intervention efficacy (Gerber et al, 2017; Singh and Bunyak, 2019).…”
Section: Discussionmentioning
confidence: 99%